PERANAN KARANG TARUNA DALAM PELESTARIAN BUDAYA SINOMAN - Sri Utami; Muhammad Syukurman; Fatimah AS (Jurusan Pendidikan Masyarakat Fakultas Keguruan Ilmu Pendidikan Universitas Siliwangi, 2023)
This research is based on the phenomenon that found in Sinoman Karang Taruna Cahya Muda Dusun Tiga Taman Sari, regarding Sinoman culture which must be pursued by local teenagers, especially Karang Taruna youth. However, this is not supported by the presence of teenagers and even members of Karang Taruna participating in presenting Sinoman culture in Sungai Sahut Village. The aim of this research is to describe the forms of participation of Karang Taruna members in Sinoman Cultural Preservation activities. This research uses a qualitative method with a case study approach, data collection techniques using observation, interviews and documentation, determining research informants using purposive sampling techniques, data analysis techniques are data reduction, data display, data verification. Based on the research results, it can be seen that the activities Karang Taruna in preserving Sinoman culture in Tiga Taman Sari Hamlet, Sungai Sahut Village, Tabir Selatan District, Merangin Regency, still has several obstacles. It is carrying out Karang Taruna activities which are caused by Karang Taruna members themselves, such as being less active and less participating in carrying out The task of the Karang Taruna is especially in Sinoman activities, while the effort that can be given by the Karang Taruna chairman in the Sinoman activity itself is by imposing fines with a nominal value determined by the Karang Taruna chairman by mutual agreement, where the fine money can be used to increase cash. youth organizations which in the future can be used for useful things. It can be concluded that Sinoman Culture is a routine activity that has been passed down from generation to generation which must still be preserved and pursued by the younger generation. it can be suggested from this research is increasing the assertiveness of the Karang Aruna Chair towards members but in a way that is easy for members to understand and understand.